Implementation Of Rahn Financing Contract In The Perspective Of Islamic Economics And The Suitability Of The Rahn Contract At BMT NU Branch Bungatan Situbondo - Faiqotul Jannah; Himami Firdausi; Zainur Ridho; Achmad Basofitrah (Universitas Nurul Jadid, 2025)
In this study focuses on the implementation and suitability of the rahn contract at BMT NU Bungatan Situbondo branch, the purpose of this study is to determine the implementation of the rahn contract at BMT NU Bungatan Branch whether it is included in the Islamic economic perspective, the theory used in this study uses the concept of fiqh muamalah, the legal basis of the Qur'an and hadith. This research uses descriptive qualitative, namely examining data in depth using primary and secondary data in the technique of documenting, interviewing, and observation. The result of this study is the implementation of the rahn contract financing, the member has agreed with what has been submitted to the BMT NU, after the BMT gives money to the member, this is where the agreement has taken effect when handing over the rahn money and valuables as evidence, from the BMT asking for ujroh by fulfilling the terms and conditions of the rahn contract. The conclusion is that the implementation of the rahn contract at BMT NU Bungatan Branch is in accordance with the terms and conditions of the rahn contract.